The Existence of The Kele Dance in The Ciamis Regency Community - Dwi Rahmalia Nur’aini; Yuliawan Kasmahidayat; Agus Supriyatna (Prodi Antropologi Fakultas Ilmu Budaya Universitas Diponegoro, 2026)
This study aims to examine the presence on the background of the creation of the Kele Dance, its existence within the Ciamis Regency community, and the factors that support and hinder its sustainability, drawing on perspectives from dance anthropology and urban anthropology. This study employed a qualitative method with a descriptive approach. Data were collected through observation, interviews, documentation and a review of relevant literature. The informants included a choreographer, a dancer, and a community activist, selected to data source triangulation. The findings indicate that the Kele Dance was created in 2006 by Raden Rachmajati Nilakoesoemah (Neng Peking). The Kele Dance was inspired by traditional activities of the Ciamis community in the past, particularly the practice of collecting water from natural springs using kele (bamboo containers). The existence of the Kele Dance continues to be maintained, as indicated by its relatively consistent performance frequency. Factors supporting the sustainability of the Kele Dance include the active contributions of the choreographer, the regeneration of dancers within local studios (sanggar), the participation of younger generations, and the flexibility of its performance contexts. Meanwhile, inhibiting factors include changes in policymakers, insufficient dissemination to the wider community, and restricted distribution of learning resources.